The Role of Sutan Sjahrir in the Jong Indonesia Organization in Support of Indonesian Independence - Aswa Adipayana; I Made Ratih; Ageng Sanjaya (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study discusses the significant role of Sutan Sjahrir in the Jong Indonesia organization as part of the struggle for Indonesian independence. Sutan Sjahrir, a young intellectual and nationalist figure, is known as one of the ten pioneering youths in the establishment of Jong Indonesia, which later changed its name to Pemuda Indonesia. This organization became the driving force behind the birth of the Youth Pledge in 1928, an important milestone in uniting the spirit of nationalism across regions and ethnicities. This study uses a historical method with the stages of heuristics, verification, interpretation, and historiography. Data were obtained through literature studies of primary sources such as books by Rudolf Mrazek and Y.B. Mangunwijaya, as well as secondary sources from scientific journals and relevant documents. The results of the study show that Sjahrir played an important role not only as the initiator of the organization, but also as the driver of the idea of national unity through an intellectual approach and social movements. Through his activities in education, journalism, and youth organizations, Sjahrir was able to spread progressive ideas that challenged colonialism and inspired a spirit of nationalism among the younger generation. His role in building the foundation of modern nationalist thought and non-violent struggle is an important legacy for Indonesia's journey to independence.